Disruption of Folate Metabolism Causes Poor Alignment and Spacing of Mouse Conceptuses for Multiple Generations - Wilkinson, Amy L.; Menelaou, Katerina; Rakoczy, Joanna; Tan, Xiu S.; Watson, Erica D. (Frontiers in Cell and Developmental Biology, 2021)
Abnormal uptake or metabolism of folate increases risk of human pregnancy complications, though the mechanism is unclear. Here, we explore how defective folate metabolism influences early development by analysing mice with the hypomorphic Mtrrgt mutation. MTRR is necessary for methyl group utilisation from folate metabolism, and the Mtrrgt allele disrupts this process. We show that the spectrum of phenotypes previously observed in Mtrrgt/gt conceptuses at embryonic day (E) 10.5 is apparent from E8.5 including developmental delay, congenital malformations, and placental phenotypes. Notably, we report misalignment of some Mtrrgt conceptuses within their implantation sites from E6.5. The degree of misorientation occurs across a continuum, with the most severe form visible upon gross dissection. Additionally, some Mtrrgt/gt conceptuses display twinning. Therefore, we implicate folate metabolism in blastocyst orientation and spacing at implantation. Skewed growth likely influences embryo development since developmental delay and heart malformations (but not defects in neural tube closure or trophoblast differentiation) associate with severe misalignment of Mtrrgt/gt conceptuses. Typically, the uterus is thought to guide conceptus orientation. To investigate a uterine effect of the Mtrrgt allele, we manipulate the maternal Mtrr genotype. Misaligned conceptuses were observed in litters of Mtrr+/+, Mtrr+/gt, and Mtrrgt/gt mothers. While progesterone and/or BMP2 signalling might be disrupted, normal decidual morphology, patterning, and blood perfusion are evident at E6.5 regardless of conceptus orientation. These observations argue against a post-implantation uterine defect as a cause of conceptus misalignment. Since litters of Mtrr+/+ mothers display conceptus misalignment, a grandparental effect is explored. Multigenerational phenotype inheritance is characteristic of the Mtrrgt model, though the mechanism remains unclear. Genetic pedigree analysis reveals that severe conceptus skewing associates with the Mtrr genotype of either maternal grandparent. Moreover, the presence of conceptus skewing after embryo transfer into a control uterus indicates that misalignment is independent of the peri- and/or post-implantation uterus and instead is likely attributed to an embryonic mechanism that is epigenetically inherited. Overall, our data indicates that abnormal folate metabolism influences conceptus orientation over multiple generations with implications for subsequent development. This study casts light on the complex role of folate metabolism during development beyond a direct maternal effect.